Thermal field theories : proceedings of the 2nd Workshop on Thermal Field Theories and Their Applications, Tsukuba, Japan, July 23-27, 1990 - Ezawa, Hiroshi, 1932-2023; Arimitsu, Toshihiko, 1952-; Hashimoto, Yukio (North-Holland delta series., 1991)
Theories of quantum fields at non-zero temperature have been steadily developed for well over a decade. In 1988, as a result of the increased demand for communication among theorists working in different fields ranging from condensed matter physics to high energy physics and astrophysics, the first international meeting was organized (the proceedings of which have been published in Physica A 158, 1989). This 2nd workshop covers similar fields, namely equilibrium and non-equilibrium statistical physics, quantum optics, high-temperature gauge-field theories, string theories, statistical theories of gravitation and cosmology. The resulting proceedings reflect the progress made in the respective fields, identify the major common problems and suggest possible directions for their solutions.